A missiological investigation of the role of the Church of Christ's medical missions at Mashoko, Zimbabwe, as transformational development - Mudzanire, Suspicion (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.